Iklan

Iklan

Nirmala F

04 Mei 2020 14:03

Pertanyaan

diketahui g(x)=2x+3 dan f(x)=x²-4x+6.maka (fog) (x)=


9

Jawaban terverifikasi

Iklan

Iklan

Tohodo S

05 Mei 2020 06:44

Jawaban terverifikasi

(fog)(x) = f(g(x)) = f(2x+3) = (2x+3)^2 - 4(2x+3)+6 = 4x^2 + 12x - 8x +9 -12 +6 = 4x^2 + 4x +3 maaf kalo salah


Iklan

Iklan

Tohodo S

05 Mei 2020 06:47

Jawaban terverifikasi

(fog)(x) = f(g(x)) = f(2x+3) = (2x+3)^2 - 4(2x+3)+6 = 4x^2 + 12x - 8x +9 -12 +6 = 4x^2 + 4x +3 maaf kalo salah


Tohodo S

05 Mei 2020 06:50

Jawaban terverifikasi

(fog)(x) = f(g(x)) = f(2x+3) = (2x+3)^2 - 4(2x+3)+6 = 4x^2 + 12x - 8x +9 -12 +6 = 4x^2 + 4x +3 maaf kalo salah


Tohodo S

05 Mei 2020 07:10

Jawaban terverifikasi

(fog)(x) = f(g(x)) = f(2x+3) = (2x+3)^2 - 4(2x+3)+6 = 4x^2 + 12x - 8x +9 -12 +6 = 4x^2 + 4x +3


Nadiyah W

07 Mei 2020 04:38

Jawaban terverifikasi

(fog) (x) =f(g(x)) = x²-4x+6 =(2x+3)²-4(2x+3)+6 =4x²+12x-9-8x-12+6 =4x²+4x+3


Intann I

10 Mei 2020 13:35

Jawaban terverifikasi

(fog)(x)= f(g(x)) = f (2x + 3) = (2x + 3)^2 - 4(2x+3)+6 = 4x^2 + 12x + 9 -8x -12 + 6 = 4x^2 + 4x + 3


Leony M

05 Mei 2020 01:37

(fog)(X)= f(g(x)) =f( 2x+3) =x²-4x+6(2x+3) =x²-8x²+18 =-7x²+18 maaf kalau salah semoga membantu


Martadewiari M

10 Mei 2020 10:51

4x²+4x+3


Maskskdkjd A

23 April 2022 20:39

test


Mau pemahaman lebih dalam untuk soal ini?

Tanya ke Forum

Tanya ke Forum

Roboguru Plus

Chat Tutor

Iklan

Iklan